Programação de computadores e processos auxiliares da aprendizagem: o caso de alunos da escola de hackers - Batistela, Fernanda (2015)
This work is in consonance with the research line Educational and Language Processes of the stricto sensu graduate studies program in Education (PPGEDU) and with the research line Technologies and Methodologies in Digital Inclusion of the Group of Study and Research in Digital Inclusion, both from the University of Passo Fundo. Its objective is, by theoretical-pedagogical contributions and field research, to analyze how computer programming, the focus of the Project School of Hackers, influences the auxiliary processes of learning proposed by Juan Ignacio Pozo. The Project consists of a set of actions that nurture the learning techniques and programming skills, using the software Scratch, for students from 6th to 9th years of Elementary School and for teachers of Municipal Elementary Schools from Passo Fundo. The technical procedures used, such as the research methodology, were bibliographic research in most part books and data collection instruments, interviews with the management team, the participant students of the Project developed in the Notre Dame School, the coordinator of the Informatics Laboratory, the Mathematics and Portuguese Teachers of the School and the monitors; monthly questionnaires to the management team, coordinators and monitors; reading of the students registration forms; participation in meetings with the project s organizing committee; monitoring and observing class memories from the School s monitors, being the researcher s main universe the observation of an eleven students group of the Notre Dame School, during seven months, weekly, at a reverse shift of the participants school activities. The theoretical background, who formed the basis to the discovery of the analysis categories, which are the four auxiliary learning processes, was Juan Ignacio Pozo, in his book Aprendices y Maestros: La Nueva Cultura Del Aprendizaje. This way, the analysis process lined in the four auxiliary processes of learning, motivation, attention, recuperation and transference and the conscience, along with the documents collected in field resulted in 1065 perceptions, which 466 were manifested by the motivation, in the first category of analysis and first auxiliary process of learning, when the students demonstrated a major influence in learning by extrinsic reasons, by the satisfaction of having learned; or extrinsic, for avoiding something undesired or to reach something desired, in exchange of learning. Still, by expectations of success or failure that the students were expecting from themselves, or then, in that the others were expecting from a student and, still, by intervention, in the moment that the monitors intervened in the learning of the students and motivated them to program, in this context of the School of Hackers, as a new learning culture